EFFECT OF TEMPERATURE ON POTASSIUM ADSORPTION-DESORPTION IN SOME IRAQ SOILS - M. M.A.Alobidi; A. Al-Zubaidi (Mesopotamia Journal of Agriculture)
This work was conducted to study potassium-adsorption-desorption in isotheam calcareau soil of Northern Iraq at three different levels of temperature 278, 298, 318 kº, from the obtained data, The adsorption-desorption curves had been constructed according to first order reaction, The results showed that the increase ot temperature from 278 to 318 kº caused an increase in the rate of coeffient adsorption (11x10-3-18.10-3 min-1) and rate coeffient of desorption from 5.2x10-3 to 7.2x10-3 min-1. The result also showed activation energy adsorption process is less than Ea of desorption, and of processes were control by diffusion process, free energy were negative and decreased with temperature increases.